Instability in the dividend policy of the Istanbul Stock Exchange (ISE) corporations: Evidence from an emerging market - Adaoglu, Cahit (Elsevier, 2000)
Dividend policy behaviour of corporations operating in emerging markets is significantly different from the widely accepted dividend policy behaviour of corporations operating in developed markets. This study provides evidence from the Istanbul Stock Exchange (ISE), an emerging European stock market, and analyses empirically whether the ISE corporations follow stable cash dividend policies in a regulatory environment that imposed mandatory dividend policies. Unlike the empirical results supporting the stable dividend policy behaviour of corporations operating in developed markets, the empirical results show that the ISE corporations follow unstable cash dividend policies and the main factor that determines the amount of cash dividends is the earnings of the corporation in that year. © 2000 Elsevier Science B.V. All rights reserved.
Keywords: Dividend policy; Istanbul Stock Exchange; Regulations; Stability